2014
DOI: 10.1089/chi.2014.0062
|View full text |Cite
|
Sign up to set email alerts
|

A Qualitative Study of Successful Adolescent and Young Adult Weight Losers: Implications for Weight Control Intervention

Abstract: Results from this study highlight considerations for future adolescent weight control treatment development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
81
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(83 citation statements)
references
References 27 publications
2
81
0
Order By: Relevance
“…On the contrary, friends who joined as workout buddies were motivating for several participants, as well as family and friends who provided positive feedback. These findings correspond well to previous studies and the theories about non-controlling, autonomy supporting feedback in SDT (Deci & Ryan, 1986; Jensen et al, 2014). The sense of belonging also played a vital role as a foundation for discussions and reflections, especially in the HLC group.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…On the contrary, friends who joined as workout buddies were motivating for several participants, as well as family and friends who provided positive feedback. These findings correspond well to previous studies and the theories about non-controlling, autonomy supporting feedback in SDT (Deci & Ryan, 1986; Jensen et al, 2014). The sense of belonging also played a vital role as a foundation for discussions and reflections, especially in the HLC group.…”
Section: Discussionsupporting
confidence: 92%
“…There seems to be a common opinion that weight management is a personal responsibility, and that individuals will start to reduce weight if the feeling of guilt for being obese is strong enough (Vartanian & Smyth, 2013). However, previous studies recognized improved health, feeling of self-worth, encouragement and engagement from friends and family members to be important factors among adolescents who successfully had lost weight (Jensen et al, 2014; Rees et al, 2014). In another study, physical appearance, pressure from the social environment or guilt was found to be the important motivator (O’Dougherty, Kurzer, & Schmitz, 2010).…”
mentioning
confidence: 98%
“…A qualitative study of 22 US overweight adolescents, identified via health centre records, found those whose BMI decreased over a 2-year period were more likely to describe 'transformative experiences' and family support as well as intense daily exercise. 4 Other qualitative studies have identified successful weight loss maintenance strategies including dietary change, 'overwhelmingly increased' exercise and rigorous self-correction after going 'off course' among US 14-20 years with sustained weight loss, 28 and a 'healthy obsession' with monitoring food, activity and weight among eight formerly obese US adolescents who had attended an immersion treatment. 29 A qualitative study of 20 overweight Taiwanese nursing students highlighted 'the struggle', of continuing to practise a new lifestyle and so reducing/maintaining bodyweight.…”
Section: Discussionmentioning
confidence: 99%
“…Weekly treatment supervision meetings were held to ensure adherence to the treatment protocol. Group sessions were standardized by using a 12-week modular behavioral weight control program developed by Jelalian et al [23] that included important components of weight management including self-monitoring, portion control, problem solving, stimulus control, emotional eating, and physical activity. Each parent/adolescent dyad also received 15 minutes of individual family intervention every 4 weeks after group sessions.…”
Section: Methodsmentioning
confidence: 99%